Micromechanics and Nanomechanics of Composite Solids - Meguid, Shaker A.; Weng, George J. (Springer International Publishing : Imprint: Springer, 2018)
This book elucidates the most recent and highly original developments in the fields of micro- and nanomechanics and the corresponding homogenization techniques that can be reliably adopted and applied in determining the local properties, as well as the linear and nonlinear effective properties of the final architecture of these complex composite structures. Specifically, this volume, divided into three main sections-Fundamentals, Modeling, and Applications-provides recent developments in the mathematical framework of micro- and nanomechanics, including Green's function and Eshelby's inclusion problem, molecular mechanics, molecular dynamics, atomistic based continuum, multiscale modeling, and highly localized phenomena such as microcracks and plasticity. It is a compilation of the most recent efforts by a group of the world's most talented and respected researchers. Ideal for graduate students in aerospace, mechanical, civil, material science, life sciences, and biomedical engineering, researchers, practicing engineers, and consultants, the book provides a unified approach in compiling micro- and nano-scale phenomena. · Elucidates recent and highly original developments in the fields of micromechanics and nanomechanics and the corresponding homogenization techniques; · Includes several new topics that are not covered in the current literature, such as micromechanics of metamaterials, electrical conductivity of CNT and graphene nanocomposites, ferroelectrics, piezoelectric, and electromagnetic materials; · Addresses highly localized phenomena such as coupled field problems, microcracks, inelasticity, dispersion of CNTs, synthesis, characterization and a number of interesting applications; · Maximizes readers' ability to apply theories of micromechanics and nanomechanics to heterogeneous solids; · Illustrates the application of micro- and nanomechanical theory to design novel composite and nanocomposite materials.